2017
DOI: 10.1159/000475713
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Causal Role of Leptin in Alzheimer Disease: A Mendelian Randomization Study

Abstract: Background: Observational evidence regarding the role of leptin in Alzheimer disease (AD) is conflicting. We sought to determine the causal role of circulating leptin and soluble plasma leptin receptor (sOB-R) levels in AD using a separate-sample Mendelian randomization study. Methods: Single nucleotide polymorphisms (SNPs) independently and solely predictive of log-transformed leptin (rs10487505 [LEP], rs780093 [GCKR], rs900400 [CCNL1], rs6071166 [SLC32A1], and rs6738627 [COBLL1]) and of sOB-R (rs1137101 [LEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Previous results demonstrate the relationship of leptin with the development of Alzheimer's. However, further research is needed to clarify whether leptin is a modifier of Alzheimer's disease or a genetic target for it (ROMO;SCHOOLING, 2017;SANTOS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results demonstrate the relationship of leptin with the development of Alzheimer's. However, further research is needed to clarify whether leptin is a modifier of Alzheimer's disease or a genetic target for it (ROMO;SCHOOLING, 2017;SANTOS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Among these adipokines, the signaling of leptin has gained considerable scientific attention as a potential therapy and biomarker for AD (ROMO;SCHOOLING, 2017). Leptin has demonstrated neurobiological effects that go beyond their role in body mass and systemic metabolism regulation, and as such act upon memory and plasticity (BONDA et al, 2014;HARVEY, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the LEPR screening, we also found several SNPs showing statistically significant associations with leptin levels in our population. These results are relevant because they highlight the pitfalls of using SNPs or GRS, derived from the above mentioned GWAS [37], as proxies for plasma leptin concentrations for setting individual-level metrics of genetic risk in Mendelian randomization studies [75], in this, and other populations (i.e., the SNPs obtained in the GWAS undertaken by Kilpeläin et al [37], have been used in Mendelian randomization studies for the association between leptin and Alzheimer’s disease [40] or bone mineral density [41]).…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish Mediterranean population is, in general, little represented in GWAS, including those carried on European populations, and so specific studies must be undertaken on that population before directly using the SNPs or GRS derived from those GWAS. Specifically, in the case of leptin levels, various studies on different populations [40,41] are using the SNPs reported in the Kilpeläin et al [37] GWAS as plasma leptin level proxies for Mendelian randomization studies. Therefore, the aims of our study for the whole population and by sex are as follows: (1) to estimate the association between the SNPs reported as most relevant (in/near the LEP, SLC32A1, GCKR, CCNL, COBLL1, and FTO genes) in the Kilpeläin et al [37] GWAS and leptin levels in a Mediterranean population; (2) to investigate whether other SNPs (after the whole gene-screening) in the 6 genes reported by Kilpeläin et al [37], plus one that we have added—the LEPR gene—are more highly associated with leptin levels in this population; and (3) to undertake a new GWAS for plasma leptin levels in this Mediterranean population.…”
Section: Introductionmentioning
confidence: 99%
“…(4144) Additionally, reports on association between leptin levels and cognitive function or AD are highly contradictory and this association needs to be further explored. (45, 46) Nevertheless, the model of independent neural and neurohumoral arms that contribute to bone loss in individuals with AD is perhaps oversimplified. The relationship between leptin and bone are far more complex than initially proposed in earlier animal experiments.…”
Section: Discussionmentioning
confidence: 99%